Azocompostos discóticos: propriedades mesomórficas e fotoresponsívas - Santos, Gustavo Sérgio dos (2019)
Liquid crystals (CLs) have a range of unique properties, which make it possible to use them in many industrial and scientific applications. By combining the attributes of the CLs with those of azobenzene, a substance known to be a reversible photoisomerization, new possibilities of application are emerging, such as in lightresponsive chromophores, photo-directed computers, nanostructure controllers, micro electromechanical systems, among others. With this idea in mind, this work describes tthe planning, synthesis, characterization and studies of the mesomorphic and photophysical properties of different organic compounds with discotic anisometry and containing the azo group in its structure. The different final products differ primarily according to the size of the center, number and type of peripheral aliphatic chains and the functional linker group: ester, amide or 1,3,4-oxadiazole. Seven final products were prepared and had some thermal and liquid-crystalline properties investigated by TGA, MOLP and DSC. All the products presented high thermal stability, being this variable slightly depending on the type of chain and the groups connectors. Compounds with the reduced rigid center did not exhibit liquid-crystalline behavior, independently of the linker group and the aliphatic chain type (linear or branched) employed. However, the mesomorphism was stabilized by the expansion of the center and the increase in the number of peripheral chains from 5 to 6, observing textures typical of columnar mesophores when analyzed by MOLP. In addition, DSC analysis ratified the liquid-crystalline behavior by the presence of additional peaks of phase transitions. Exchange of the functional linker groups altered the melting point and stability of the mesophases, following the order of ester <1,3,4-oxadiazole amide. All seven had their Photoisomerization in solution confirmed by UV-Vis measurements and, in some cases, ¹H NMR. The rapid Photoisomerization process and its reversibility enable materials prepared for future applications.